Ilha interdisciplinar de racionalidade com o tema "Churrasco saudável": promovendo alfabetização científica e tecnológica no Ensino Fundamental II - Gobbi, Andréia Michelon (My University, 2021)
This paper presents the development and results of a research in Science and Mathematics Teaching, which aimed to verify the occurrence of the attributes of Scientific and Technological Literacy (STL) - autonomy, dominance and communication, through a research of the type pedagogical intervention, that made use of the method of construction of an Interdisciplinary Island of Rationality (IIR), by Gérard Fourez. The theme of the IIR entitled "Healthy Churrasco" was problematized, in order to instigate the curiosity of the students for the subject, because it is part of the cultural characteristics of Rio Grande do Sul (RS), state in which the school where this work was developed is based. The activities surrounding the construction of IIR took place in an 8th grade class of Elementary School II, a school located in a context of social vulnerability, in the first semester of 2017. The research is within the line "Foundations and Educational Strategies in the Teaching of Sciences and Mathematics," proposed in the Master's Degree in Teaching Science and Mathematics of the University of Caxias do Sul and aims to: investigate, evaluate and implement educational strategies in the light of the foundations of education. It is described as a research of the type pedagogical intervention, qualitative and applied nature, being descriptive as to the objectives. The corpus, coming from the activities carried out at the school demonstrated evidence that it was possible to work interdisciplinary, through the proposed theme, from the construction of the IIR, in the curricular component of Portuguese Language. In addition, it conferred the development of the attributes of the STL: the autonomy for the organization of activities in groups and research, the domain of the contents/information on the chosen topic and the relations of these with the everyday/reality, as well as the communication of what was learned in different situations experienced. As an educational product this dissertation presents a didactic guide so that other teachers can apply pedagogical interventions using the IIR methodology in Basic Education. [resumo fornecido pelo autor]
Este trabalho apresenta o desenvolvimento e os resultados de uma investigação em Ensino de Ciências e Matemática, que teve por objetivo verificar a ocorrência dos atributos da Alfabetização Científica e Tecnológica (ACT) - autonomia, domínio e comunicação, por meio de uma pesquisa do tipo intervenção pedagógica, que fez uso do método de construção de uma Ilha Interdisciplinar de Racionalidade (IIR), de Gérard Fourez. O tema da IIR intitulado "Churrasco saudável" foi problematizado, de modo a instigar a curiosidade dos estudantes pelo assunto, pois faz parte das características culturais do Rio Grande do Sul (RS), estado em que se localiza a escola em que este trabalho foi desenvolvido. As atividades em torno da construção da IIR se deram em uma turma de 8º ano do Ensino Fundamental II, de uma escola situada em um contexto de vulnerabilidade social, no primeiro semestre letivo de 2017. A pesquisa está dentro da linha "Fundamentos e Estratégias Educacionais no Ensino de Ciências e Matemática", proposta no Mestrado Profissional em Ensino de Ciência e Matemática da Universidade de Caxias do Sul e tem por objetivo: investigar, avaliar e pôr em prática estratégias educacionais à luz dos fundamentos da educação. Caracteriza-se como uma pesquisa do tipo intervenção pedagógica, qualitativa e de natureza aplicada, sendo descritiva quanto aos objetivos. O corpus, proveniente das atividades realizadas na escola demonstrou evidências de que foi possível trabalhar a interdisciplinaridade, por meio do tema proposto, a partir da construção da IIR, no componente curricular de Língua Portuguesa. Além disso, conferiu o desenvolvimento dos atributos da ACT: a autonomia para a organização das atividades em grupos e investigação, o domínio dos conteúdos/informações sobre o tema escolhido e as relações destes com o cotidiano/realidade, bem como a comunicação do que foi aprendido em diferentes situações vivenciadas. Como produto educacional esta dissertação apresenta um guia didático para que outros professores possam aplicar intervenções pedagógicas utilizando a metodologia das IIR na educação básica. [resumo fornecido pelo autor]
Keywords: Alfabetização; Ciência e tecnologia; Língua portuguesa; Ensino fundamental; Literacy; Science and technology; Portuguese language; Elementary School